Honey-Induced Protein Stabilization as Studied by Fluorescein Isothiocyanate Fluorescence. (9th October 2013) - Wong, Yin How; Abdul Kadir, Habsah; Tayyab, Saad
Abstract : Protein stabilizing potential of honey was studied on a model protein, bovine serum albumin (BSA), using extrinsic fluorescence of fluorescein isothiocyanate (FITC) as the probe. BSA was labelled with FITC using chemical coupling, and urea and thermal denaturation studies were performed on FITC-labelled BSA (FITC-BSA) both in the absence and presence of 10% and 20% (w/v) honey using FITC fluorescence at 522 nm upon excitation at 495 nm. There was an increase in the FITC fluorescence intensity upon increasing urea concentration or temperature, suggesting protein denaturation. The results from urea and thermal denaturation studies showed increased stability of protein in the presence of honey as reflected from the shift in the transition curve along with the start point and the midpoint of the transition towards higher urea concentration/temperature. Furthermore, the increase in Δ G D H 2 O and Δ G D 25 ∘ C in presence of honey also suggested protein stabilization.